2022
DOI: 10.26434/chemrxiv-2022-jh9d6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing dissolved CO2(aq) in aqueous solutions for CO2 electro-reduction and storage

Abstract: CO2 dissolved in aqueous solutions is of wide ranging importance from CO2 capture, storage and photo-/electro-reduction in the fight against global warming, to CO2 analysis in various liquids including natural waterbodies and consumer drinking products. Here we developed micro-scale infrared (IR) spectroscopy for in-situ dynamic monitoring and quantitating CO2(aq) in aqueous solutions with high time resolutions under various conditions including CO2 gas bubbling and high pressures. The quantized CO2(g) rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…), 57,58 our plateau value (∼1000 ppm) is in the range of those reported in literature at the same pH values. 58 The initial boost in the dissolved CO 2 (Figure 3) with NiNPs, together with the variation of hydronium concentration (Figure 2b) suggest the co-presence of multiple mechanisms when NiNPs are present in the solution, which are discussed below.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…), 57,58 our plateau value (∼1000 ppm) is in the range of those reported in literature at the same pH values. 58 The initial boost in the dissolved CO 2 (Figure 3) with NiNPs, together with the variation of hydronium concentration (Figure 2b) suggest the co-presence of multiple mechanisms when NiNPs are present in the solution, which are discussed below.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…4e, Supplementary Note 22). 26 Importantly, we identified that [CO2] ≥ 0.2 mol L -1 unlocks the C1-C2 coupling reaction to form C3 products, which emphasizes the benefit of performing the CO2RR in the supersaturated electrolyte. 33 To discriminate the role of CO2, we systematically examined the CO2RR performance of CO2-10-Cu94Ag6 with and without supersaturation as well as the influence of the current density for the codeposition of the alloy (Supplementary Fig.…”
Section: Co2rr Under Atmospheric Pressured Co2 Supersaturationmentioning
confidence: 71%
“…18, Supplementary Note 16). 26 Electrochemical activation was carried out before the reaction to remove the surface oxides (Supplementary Fig. 19, Supplementary Note 17).…”
Section: Co2rr Under Atmospheric Pressured Co2 Supersaturationmentioning
confidence: 99%